2010
DOI: 10.1007/s00234-010-0672-y
|View full text |Cite
|
Sign up to set email alerts
|

Complication rate in unprotected carotid artery stenting with closed-cell stents

Abstract: Our clinical outcome demonstrates that unprotected CAS with small cell designed stents results in a very low procedural complication rate, which makes the use of a protection device dispensable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 29 publications
0
21
0
1
Order By: Relevance
“…These reports included symptomatic and asymptomatic patients, with an average degree of stenosis ranging from 80% to 82%. [12][13][14][15] In our series, all cases were symptomatic except 9, and the mean degree of stenosis was 89%. In addition, our report included the largest number of symptomatic patients and the highest degree of stenosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These reports included symptomatic and asymptomatic patients, with an average degree of stenosis ranging from 80% to 82%. [12][13][14][15] In our series, all cases were symptomatic except 9, and the mean degree of stenosis was 89%. In addition, our report included the largest number of symptomatic patients and the highest degree of stenosis.…”
Section: Discussionmentioning
confidence: 99%
“…The need for predilation is variable according to reports (2%-46%), [11][12][13] suggesting that it depends heavily on the experience and methodology of the operator. According to our experience, it is possible to navigate with the stent device system without predilation in most cases.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding prior stroke as a risk factor for CHS, many authors have found that diseases like diabetes mellitus or longstanding pre-existing hypertension in which microangiopathy affects the endothelium of small vessels predispose to hyperperfusion and CHS (Chamorro et al, 2000;McCabe et al, 1999;Naylor et al, 2003;van Mook et al, 2005). Tietke et al (2010) analyzed the outcomes of 358 patients treated with CAS using small closed-cell stents without distal protection. The peri-interventional and 30-day mortality/stroke rate was 4.19% (15/358).…”
Section: Extracranial Carotid Angioplastymentioning
confidence: 99%
“…Many neuroradiologists feel that this is not a good option as their local experiences with CAS are much better than the results that have emerged from the trials. An example is reported in a single-centre experience within this issue [4]. However, is such data useless since operators tend to be favourable in assessing their outcome [5]?…”
mentioning
confidence: 99%